Teleguidance for Patient Self‐Imaging of Hemophilic Joints Using Mobile Ultrasound Devices: A Pilot Study. (19th August 2022) - Aguero, Peter; Barnes, Richard FW; Flores, Andres; von Drygalski, Annette
Abstract : Background: Teleguidance on portable devices opens the possibility of joint self‐imaging in persons with hemophilia (PWH). Aims: Determine the feasibility of patient self‐imaging with/without teleguidance. Methods: Adult PWH received ultrasound teaching including 11 views for hemarthrosis detection in ankles, elbows, and knees. The patients acquired five randomly selected views with the Butterfly/IQ probe without assistance at 2, 6–8 weeks, and 3–4 months later, followed by teleguidance. Image acquisition was timed, patients identified anatomic landmarks, and image quality was graded. Questionnaires assessed the imaging experience. Hemophilia Joint Health Score (HJHS) indicated arthropathy status. Results: Of 132 PWH, 10 (median age 52 years) opted for study inclusion. Most had severe Hemophilia A, were white/non‐Hispanic, with at least a high school degree and, overall, similar to the other 122 PWH. At 2 and 6 weeks after training, ~80% images were acquired correctly compared with 53% at 12 weeks. Accuracy of landmark recognition was ~55%. With teleguidance, all images were acquired correctly, with near‐perfect image quality ( P  ≤ .01 compared with the 3–4 month time point). Median HJHS of scanned joints was 11.5 at each time point, demonstrating a similar spectrum of arthropathic changes. Median time of image acquisition was fast, and similar with or without teleguidance (median 01:04 [mm:ss] vs median 01:02), but differed slightly between arthropathic and non‐arthropathic joints. Study participants and the imaging facilitator rated that it was easy to navigate mobile technology and acquire images with teleguidance. Conclusion: Mobile ultrasound with teleguidance for joint self‐imaging is feasible and warrants further exploration.